DETECTION OF ADULTERATION, CHEMICAL COMPOSITION AND HYGIENIC STATUS OF MILK SUPPLIED TO VARIOUS CANTEENS OF EDUCATIONAL INSTITUTES AND PUBLIC PLACES IN FAISALABAD - Faraz; A.; M. Lateef; M. I. Mustafa; P. Akhtar; M. Yaqoob; S. Rehman (Journal of Animal and Plant Sciences, 2013)
This study was designed to elaborate the hygienic status of milk supplied to educational institutions (EI) and public places (PP) in the Faisalabad. A total of sixty samples were collected from the different location and were processed for determination of adulterants, chemical composition and hygienic condition. The results indicated that water was added to 97% and 93% samples from EI and PP respectively. The urea, formalin and cane sugar were detected in 63, 87; 23, 27 and 87, 97 percent samples each from EI and PP, respectively. 3% milk samples from canteens of various public places were found adulterated with hydrogen peroxide. No sample was found to be adulterated with starch, detergents and oil. The tests carried out for evaluating the chemical composition and physio-chemical properties of the milk samples showed the following mean values: Protein%, 1.12+0.09 and 1.33+0.24; Fat%, 2.06+0.11 and 1.40+0.15; Solid-not-fat, 5.10+0.17 and 4.77+0.58; Total solids, 7.18+0.27 and 6.17+0.68; % Acidity, 0.07+0.00 and 0.07+0.00 and average Specific gravity, 1.01+0.00 and 1.01+0.00 from various canteens of EI and PP, respectively. The time for the reduction of Methylene blue dye in milk samples 0-2 Hours, 3% and 17%; 2-6 Hours, 27% and 10%; 6-8 Hours, 23% and 17%; Over 8 Hours, 47% and 56% from various canteens of EI and PP, respectively. The result depicted that samples analysed did not conform legal standards, had poor physical appearance and adulterated with chemicals injurious to health.
Keywords: Adulteration; chemical composition; hygienic status; Milk supply; Educational Institutes; Public Places